Various configurations of externally bonded strain-hardening cementitious composite reducing shear failure risk of defected RC beams - Bahrami, Alireza; Ghalla, Mohamed; Elsamak, Galal; Badawi, Moataz; Mlybari, Ehab A.; Abdelmgeed, Fathi A. (Frontiers in Materials, 2024)
This study delves into the efficacy of external strengthening methods in improving the shear behavior of deficient reinforced concrete (RC) beams that lack shear stirrups, utilizing both experimental and numerical methodologies. Failure risk of such beams is a potential threat which is mitigated carefully to increase building safety and sustainability to avoid risk of construction failure. Ten RC beams underwent three-point experimental testing to assess the influence of the strengthening scheme and the presence of mechanical anchors. Two beams were designated as control specimens, while eight beams were reinforced with the application of additional strain-hardening cementitious composite (SHCC) layer in various configurations. These configurations encompassed single-sided, two-sided, and strip applications, with the inclusion of mechanical anchors. The study found that the use of a single-sided SHCC, incorporating vertically bent bars into the RC beam, is recognized for its efficient alleviation of degradation in shear reinforcement. The incorporation of three SHCC strips to partially reinforce the compromised beams demonstrated a modest impact on the initial stiffness. Nevertheless, noteworthy enhancements of 46% and 42% were observed in both cracking and ultimate load, respectively. Furthermore, increasing the number of the SHCC strips to four resulted in a more significant improvement in the load–deflection response. Enhancing the compromised beams by attaching four SHCC strips to the beams using bolts presents a feasible alternative to the configuration where SHCC is uniformly attached along the whole defected zone. Moreover, a numerical model was created to simulate the tested beams. The model effectively anticipated the progression of cracks, ultimate capacity, and deformation, indicating excellent agreement with the experimental observations.